CHARACTERISTICS OF USING DIFFERENT TOOLS AND METHODS IN TRAINING YOUNG VOLLEYBALL PLAYERS - Yuldashev Sardorbek Adilbekovich (Galaxy International Interdisciplinary Research Journal, 2021)
The main form of training of young volleyball players is these activities, with the help of which the main tasks such as sports, fitness and education are solved. The article discusses the main tools and techniques used in the training of young volleyball players in the process of sports.